2004
DOI: 10.1246/cl.2004.1400
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dense Y-zeolite Bulks with Large Surface Area Using a Hydrothermal Hot-pressing (HHP) Process

Abstract: Highly dense and large bulk Y-zeolites (1.5 mm in thickness and 20 mm in diameter) with a significantly large surface area over 700 m2/g were obtained by a short-term hydrothermal hot-pressing (HHP) treatment at 423 K for 2 h, comparable with the Y-zeolite powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The average heating rate was about 80 º C /min and sintering time was 5 minutes in this process. The phosphates were also used as the starting powder for hydrothermal hot pressing (HHP) method [12][13][14]. The mixture of powder and water or ethanol were set in a mold and mechanically pressed with a uni-axial pressure and subsequently heated at 150 and 200 ºC for 2 hours.…”
Section: Synthesis Of Cerium Polyphosphate Bulksmentioning
confidence: 99%
“…The average heating rate was about 80 º C /min and sintering time was 5 minutes in this process. The phosphates were also used as the starting powder for hydrothermal hot pressing (HHP) method [12][13][14]. The mixture of powder and water or ethanol were set in a mold and mechanically pressed with a uni-axial pressure and subsequently heated at 150 and 200 ºC for 2 hours.…”
Section: Synthesis Of Cerium Polyphosphate Bulksmentioning
confidence: 99%
“…The discontinuity of a micropore channel network between zeolite crystals and grain boundaries was reported to be caused by the introduction of voids, pinholes and amorphous phases into the zeolite crystals. 15) The dissolution of natural zeolite is proposed to lead to the partial collapse of the microporous structure of the zeolite in the hydrothermal treatment. That is, the discontinuity of the micropore channel network causes the reduction of the micropore volume in samples after treatment.…”
Section: Jcs-japanmentioning
confidence: 99%
“…It has been reported that various inorganic materials can produce solid bodies from high-level radioactive-waste, [8][9][10] for recycling as glass powder 11-14 using HHP methods. Nakahira et al 15,16 reported that solidified Y-zeolites having high values of specific surface areas were successfully obtained by this HHP method. In this study, we report the results of synthesis of the bulky and dense mesoporous silica FSM bodies from FSM powder with and without a surfactant as a starting powder for HHP.…”
Section: Introductionmentioning
confidence: 98%